PERAN PENGEMBANGAN SUMBER DAYA MANUSIA DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI - Asep Suhada (DIALOGIKA, 2019)
This study aims to examine descriptively about the application of human resource management and work culture as well as examine verification about the effect of the application of human resources and work culture on employee performance partially and together. The research method uses descriptive and verification, the population consists of employees of PDAM Majalengka Branch with a total sampling technique. Source of data used are primary and secondary data with correlation and regression analysis techniques. Descriptive research results indicate that the application of human resource management, work culture, and performance in PDAM’ is not optimal. Verification research results prove that the application of human resource management and work culture has a significant and partially significant effect.